Hyporeflective pagetoid cells: a new clue for amelanotic melanoma diagnosis by reflectance confocal microscopy. (1st July 2014) - Losi, A.; Longo, C.; Cesinaro, A.M.; Benati, E.; Witkowski, A.; Guitera, P.; Pellacani, G.
Summary: Background: Amelanotic melanoma represents a diagnostic challenge both clinically and dermoscopically. Few studies based on case series have explored the possibility of using reflectance confocal microscopy (RCM) to diagnose amelanotic melanoma. Objectives: To validate a new confocal feature, named hyporeflective pagetoid cells (HPCs), for the diagnosis of amelanotic melanoma. Methods: A group of 20 amelanotic melanomas and a control population of nonpigmented melanocytic naevi (10), hypo/nonpigmented nonmelanocytic lesions (20) and pigmented melanomas (20), imaged by RCM, were retrospectively evaluated. The presence of HPCs and other diagnosis‐specific confocal features was assessed and correlated with histopathology. Results: HPCs were present, and usually abundant, in the majority of amelanotic melanomas (85%). As expected, they were also observed in Spitz naevi. On histopathology, they were correlated with pagetoid infiltration of hypomelanotic melanocytes in all melanocytic lesions. Few nonmelanocytic lesions (three squamous cell carcinomas, two seborrhoeic keratoses and one basal cell carcinoma) showed the presence of HPCs. In these cases, they corresponded to enlarged or dyskeratotic keratinocytes by histopathology. Conclusions: The identification of HPCs in the epidermis is a new parameter that is frequently found in amelanotic melanoma. Possible confounders are represented by atypical keratinocytes that can be present in nonmelanocytic lesions. However, the whole architecture and the presence of additional diagnostic criteria should be considered in order to obtain a correct diagnosis.